let f(x)=x^2-1, let g(x)=2x+3

Algebra
Tutor: None Selected Time limit: 1 Day

a.) find (f+g)(x)

b.) find (fg)(2)

c.)(f o g)(x)

Apr 7th, 2015

a) (f+g)(x) = X^2 - 1 + 2x + 3 = x^2 + 2x + 2

b) (fg)(x) = (x^2 - 1)(2x + 3) = 2x^3 + 3x^2 - 2x - 3

c) (fog)(x) = (2x+3)^2 - 1 = 4x^2 + 12x + 9 - 1 = 4x^2 + 12x + 8

Apr 7th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 7th, 2015
...
Apr 7th, 2015
Feb 25th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer